BIOTECHNOLOGICAL INNOVATIONS IN CROP IMPROVEMENT: HARNESSING GENETIC ENGINEERING FOR ENHANCED YIELD AND DISEASE RESISTANCE - Nino Tsereteli; Tedo Chkonia; Natia Shengelia (Techno Agriculturae Studium of Research, 2026)
Biotechnological innovations have become increasingly important in addressing global challenges related to food security, crop productivity, and plant disease pressure. Conventional breeding approaches, while effective, are often time-consuming and limited in their ability to rapidly introduce complex traits such as multi-gene disease resistance and stress tolerance. Advances in genetic engineering provide new opportunities to enhance crop yield and resilience through precise modification of plant genomes. This study aims to examine the role of genetic engineering technologies in crop improvement, with a particular focus on yield enhancement and disease resistance. The research employed a comprehensive analytical approach combining experimental evidence from transgenic and genome-edited crop trials with a systematic review of recent biotechnological applications. Key performance indicators included yield performance, resistance to major crop diseases, and agronomic stability under varying environmental conditions. The results demonstrate that genetically engineered crops exhibited significant yield improvements and enhanced resistance to targeted pathogens compared to conventionally bred varieties. Reduced disease incidence contributed to lower yield losses and improved production consistency. The study concludes that genetic engineering represents a powerful and effective tool for sustainable crop improvement when integrated with responsible management and regulatory frameworks. Biotechnological innovations hold strong potential to support resilient agricultural systems and long-term global food security.